2018
DOI: 10.1002/jcp.26568
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNAs in cancer‐immunity cycle

Abstract: The imbalance of immune status in cancer microenvironment plays an important role in the development and progression of cancer. Immunotherapy based on this has become an important field of cancer research in recent years. Many studies on long noncoding RNA (lncRNA) in cancer have focus on its regulation in cancer development and metastasis. Recent studies have suggested that lncRNAs play crucial roles in different phases of cancer immunity, including antigen releasing, antigen presentation, immune activation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
117
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 115 publications
(118 citation statements)
references
References 78 publications
1
117
0
Order By: Relevance
“…Exosomes are rich in variety of RNAs, such as mRNA, miRNAs and long non-coding RNAs (lncRNAs). LncRNAs have been well established as important regulator of the differentiation and function of T cells 10. So we want to explore the distinct lncRNA expression profile in exosomes derived from exhausted CD8+ T cells, which may help us to understand the underlying interaction of CD8+ T cells in different states and throw light on the study of dysfunctional anticancer immunity.…”
Section: Introductionmentioning
confidence: 99%
“…Exosomes are rich in variety of RNAs, such as mRNA, miRNAs and long non-coding RNAs (lncRNAs). LncRNAs have been well established as important regulator of the differentiation and function of T cells 10. So we want to explore the distinct lncRNA expression profile in exosomes derived from exhausted CD8+ T cells, which may help us to understand the underlying interaction of CD8+ T cells in different states and throw light on the study of dysfunctional anticancer immunity.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of studies have demonstrated that lncRNAs could participate in diverse biological processes by regulating genes at transcriptional, posttranscriptional, and epigenetic levels (Kornienko, Guenzl, Barlow, & Pauler, 2013). Abnormal lncRNAs expression is therefore implicated in various diseases, such as cancer (Yu, Wang, He, Xu, & Wang, 2018) and neurodegeneration disease (Szafranski, Abraham, & Mekhail, 2015). Importantly, emerging research have also found that lncRNAs serve as a new functional player in cardiovascular diseases (Shi & Yang, 2016).…”
mentioning
confidence: 99%
“…These findings indicate that SPRY4-IT1 exhibits tremendous potentiality for the diagnosis and treatment of CCA and likely functions as a novel diagnostic biomarker and intervention target. experiment was also conducted to prove its carcinogenic function (Han et al, 2018;Yu, W. D. et al, 2018;Yu, Y. et al, 2018aYu, Y. et al, , 2018b. Similar to the above, small nucleolar RNA host gene 1 (SNHG1), which is situated at 11q12.3 region of the human chromosome Zhang, D. et al, 2018;Zhang, R. et al, 2018;, was also verified highly expressed in both CCA tissues and cells.…”
mentioning
confidence: 72%